2008
DOI: 10.1210/en.2008-0447
|View full text |Cite
|
Sign up to set email alerts
|

Leydig Cells Express Follicle-Stimulating Hormone Receptors in African Catfish

Abstract: This report aimed to establish, using African catfish, Clarias gariepinus, as model species, a basis for understanding a well-known, although not yet clarified, feature of male fish reproductive physiology: the strong steroidogenic activity of FSHs. Assays with gonadotropin receptor-expressing cell lines showed that FSH activated its cognate receptor (FSHR) with an at least 1000-fold lower EC50 than when challenging the LH receptor (LHR), whereas LH stimulated both receptors with similar EC50s. In androgen rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 58 publications
7
75
1
2
Order By: Relevance
“…Irrespective of the mechanism(s) involved, our This has been shown in Japanese eel [31], African catfish [17], and zebrafish [18]. Indeed, Fsh was 23 more potent as steroidogenic hormone than Lh in both catfish [60] and zebrafish [18].…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Irrespective of the mechanism(s) involved, our This has been shown in Japanese eel [31], African catfish [17], and zebrafish [18]. Indeed, Fsh was 23 more potent as steroidogenic hormone than Lh in both catfish [60] and zebrafish [18].…”
mentioning
confidence: 64%
“…[7] and the three gonadotropin subunits (lhb, fshb, cga) [37,59], and the testicular and seminal 7 vesicle mRNA levels of the Lh receptor (lhcgr) [58] and the Fsh receptor (fshr) [6], using the ∆∆Ct 8 method. A detailed description of the rtqPCR procedure has been given previously [6,17]. Primers 9 and fluorogenic probes (Table 1), specific for the mRNAs mentioned above, or for the endogenous 10 control (catfish 28s rRNA), were designed with Primer Express software (Applied Biosystems, Foster…”
mentioning
confidence: 99%
“…The presence of Fshr has been described in the tubular compartment but also on Leydig cells in four species so far, i.e. eel, African catfish, zebrafish, and honeycomb grouper (Ohta et al 2007, Garcia-Lopez et al 2009, Alam et al 2010. These studies have suggested that the steroidogenic potency of Fsh may result from the direct action of Fsh on Leydig cells.…”
Section: Introductionmentioning
confidence: 95%
“…fed diet supplemeted with purwoceng extract kelenjar utama yang mengatur reproduksi dan spermatogenesis secara umum. Melalui sistem ini, gonadotropin pituitari, LH dan FSH mengatur testis melalui reseptor yaitu LH reseptor dan FSH reseptor (García-López et al, 2009;Schulz et al, 2008). Deteksi imunositokemikal protein reseptor FSH pada Anguilla japonica, sel Leydig, menandakan bahwa peran FSH pada spermatogenesis diatur oleh produksi androgen (Ohta et al, 2007).…”
Section: Pendahuluanunclassified